2003
DOI: 10.1139/x03-072
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and mechanical site preparation: effects onPinus contortagrowth, physiology, and microsite quality on grassy, steep forest sites in British Columbia

Abstract: Site preparation alleviates the effects of pinegrass (Calamagrostis rubescens Buckl.) interference on conifers in British Columbia, but little is known about interference mechanisms and appropriate site preparation methods for steep slopes. In this study, lodgepole pine (Pinus contorta Dougl. ex Loud.) was planted in pinegrass controls and small (90 × 90 cm) and large (180 × 90 cm) patches where (i) only pinegrass was removed using glyphosate or (ii) both pinegrass and the forest floor were removed using an ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
46
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 53 publications
8
46
0
Order By: Relevance
“…In adjacent large openings (> 0.1 ha in size with all trees removed) on the same site, Huggard et al (2005) similarly found that small patch site preparation was adequate for good survival. On another dry, cool IDF site that had been clearcut, Simard et al (2003) also found that lodgepole pine survival reached 80% in small (90 cm ϫ 90 cm) grass-free prepared patches, but that it reached 97% in larger (90 cm ϫ 180 cm) patches. Larger patches may be necessary to improve survival on clearcut sites where frost susceptibility (Fleming et al 1998) and pinegrass competition tend to be greater (Heineman et al 2003).…”
Section: Discussionmentioning
confidence: 83%
“…In adjacent large openings (> 0.1 ha in size with all trees removed) on the same site, Huggard et al (2005) similarly found that small patch site preparation was adequate for good survival. On another dry, cool IDF site that had been clearcut, Simard et al (2003) also found that lodgepole pine survival reached 80% in small (90 cm ϫ 90 cm) grass-free prepared patches, but that it reached 97% in larger (90 cm ϫ 180 cm) patches. Larger patches may be necessary to improve survival on clearcut sites where frost susceptibility (Fleming et al 1998) and pinegrass competition tend to be greater (Heineman et al 2003).…”
Section: Discussionmentioning
confidence: 83%
“…Accordingly, previous studies have shown only small differences in the effects of OM1 versus OM2 on overall bacterial and fungal communities (Hartmann et al, 2012) and small or no differences in effects on soil chemistry and tree growth (Ponder et al, 2012). The OM3 treatment, involving removal of whole trees plus forest floor, is a very severe disturbance, which was previously found to impact the overall soil microbial community due to the loss of nutrients and habitat (Simard et al, 2003;Hartmann et al, 2012). This treatment eliminated all above-ground woody biomass and was expected to have an extreme effect on hemicellulolytic populations.…”
Section: Harvesting Impacts On Hemicellulolytic Microbes Htc Leung Et Almentioning
confidence: 99%
“…Indeed, the highgrading management approach, combined with summer drought (Hamman and Wang 2006), episodic seed dispersal (Klinka et al 2000) and gap-phase disturbance regime characteristic of interior Douglas-fir forests (Klenner et al 2008), have led to variable natural regeneration across the dry climatic zones of interior Douglas-fir (Newsome et al 1991;Stark et al 2006). To augment natural regeneration, seedlings are often planted, but even they suffer from high mortality due to drought, competition from pinegrass, summer frost, tramping by cattle (Simard et al 2003), and lack of mycorrhizae at the time of planting, due to high fertilization and irrigation regimes used in commercial nurseries (Berch et al 1999). In the dry forests that interface with the grassland, survival of planted interior Douglas-fir has averaged only 40%, and at higher, wetter elevations, survival is still less than 50% where pinegrass competition and cattle grazing are not carefully controlled (but approx.…”
Section: Loss Of Complexitymentioning
confidence: 99%
“…However, colonization of non-local tree genotypes by weakly compatible local ectomycorrhizae may be an important barrier to seedling establishment and successful migration. Most temperate trees are colonized by host-specific and generalist fungal taxa, potentially forming mycorrhizal networks (Molina et al 1992;Simard et al 2002). However, research on arbuscular mycorrhizae suggests the symbiosis can range from mutualistic to parasitic depending on the specific pairings (Bever 2002;Klironomos et al 2003).…”
Section: Biotic Facilitation Of Species Migrationmentioning
confidence: 99%